The Influence of Compensation and Motivation on Teachers’ Turnover Intention at Kemala Bhayangkari 1 Senior High School in Kubu Raya Regency - Fadila, Nur; Mahdi, Irfan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of compensation and motivation on turnover intention among teachers at Kemala Bhayangkari 1 Senior High School in Kubu Raya District. Data were collected through a questionnaire distributed to all 42 permanent teachers and analyzed using multiple linear regression. The results of validity and reliability tests showed that the research instruments met the requirements. Normality, linearity, and multicollinearity tests also indicated that the data were suitable for regression analysis. The regression results showed that compensation and motivation had a negative and significant influence on turnover intention, with coefficients of -0.131 and -0.263, respectively, and significance values of 0.036 and 0.027 (p 0.05). This means that the higher the compensation and motivation received by teachers, the lower their intention to leave the school. The coefficient of determination (R²) of 0.140 indicates that 14% of the variation in turnover intention can be explained by these two variables, while the remainder is influenced by other factors. The simultaneous test (F-test) reinforces the finding that compensation and motivation together have a significant effect on turnover intention (F = 12.567; p 0.05). This study concludes that increasing compensation and motivation should be a priority for school management to reduce teacher turnover rates and maintain the quality of human resources in the education sector. Therefore, efforts to improve well-being and provide effective motivation can strengthen teachers' commitment and reduce their intention to leave their jobs.